5-HT2A Receptor Binding in the Frontal Cortex of Parkinson's Disease Patients and Alpha-Synuclein Overexpressing Mice: A Postmortem Study. (4th August 2016) - Rasmussen, Nadja Bredo; Olesen, Mikkel Vestergaard; Brudek, Tomasz; Plenge, Per; Klein, Anders Bue; Westin, Jenny E.; Fog, Karina; Wörtwein, Gitta; Aznar, Susana
Abstract : The5 - H T 2 A receptor is highly involved in aspects of cognition and executive function and seen to be affected in neurodegenerative diseases like Alzheimer's disease and related to the disease pathology. Even though Parkinson's disease (PD) is primarily a motor disorder, reports of impaired executive function are also steadily being associated with this disease. Not much is known about the pathophysiology behind this. The aim of this study was thereby twofold: (1) to investigate5 - H T 2 A receptor binding levels in Parkinson's brains and (2) to investigate whether PD associated pathology, alpha-synuclein (AS) overexpression, could be associated with5 - H T 2 A alterations. Binding density for the5 - H T 2 A -specific radioligand [ 3 H]-MDL 100.907 was measured in membrane suspensions of frontal cortex tissue from PD patients. Protein levels of AS were further measured using western blotting. Results showed higher AS levels accompanied by increased5 - H T 2 A receptor binding in PD brains. In a separate study, we looked for changes in5 - H T 2 A receptors in the prefrontal cortex in 52-week-old transgenic mice overexpressing human AS. We performed region-specific5 - H T 2 A receptor binding measurements followed by gene expression analysis. The transgenic mice showed lower5 - H T 2 A binding in the frontal association cortex that was not accompanied by changes in gene expression levels. This study is one of the first to look at differences in serotonin receptor levels in PD and in relation to AS overexpression.